Pelatihan Instalasi Dasar Sistem Operasi Linux Versi Debian Pada Siswa SMK Muhammadiyah Loa Janan - Zayni Zayni; Muhammad Taufiq Sumadi; Nauval Azmi Verdikha (BADAN PENERBIT STIEPARI PRESS, 2023)
The community service program at SMK Muhammadiyah Loa Janan focuses on installing the Debian Linux operating system and virtualization using Virtualbox. Over a three-month period, three study groups were involved by dividing two training sessions per day. The implementation method involves theory and practice with emphasis on a basic understanding of Debian Linux operating system installations. This outline reflects the challenges of students' lack of technical skills in the face of technological advances. The solution is intensive training with the support of guest teachers from the Informatics Engineering Study Program. Integrated implementation methods include material introduction, practice, and evaluation. The results noted an increase in students' understanding and skills in Debian Linux installations, with recommendations for additional resources.